Dietary supplement use in competitive Spanish football players and differences according to sex - Sousa-Rufino, C.; Pareja-Galeano, H.; Martínez-Ferrán, M. (Nutrients, 2025)
Objectives: This study aimed to evaluate and compare the consumption of dietary supplements (DS) in semi-professional male and professional female Spanish football players.